Depression in prison population: Demographic and clinical predictors - Oluyinka Emmanuel Majekodunmi; Adetunji Obadeji; Lateef Olutoyin Oluwole; Raifu Olawoye Oyelami (Wolters Kluwer Medknow Publications, 2017)
Studies have shown that mental illnesses are more common among the prison population than the general population. However, most studies in this environment had only looked at nonspecific psychiatric morbidities. The objective of this study was to assess the prevalence of major depressive disorder, its associated sociodemographic and clinical variables in a population of inmates in Nigeria. Institution-based cross-sectional study was conducted among 196 prisoners consisting of 136 awaiting trials (AT) and 60 convicted inmates (CI). Simple random sampling technique was used to select the study participants. Data were collected using a structured interviewer-administered questionnaire. Depression was assessed with the depression module of the Structured Clinical Interview Schedule for Axis 1 Diagnostic Statistical Manual-IV (DSM-IV) Disorders. The diagnosis was made according to the DSM-IV criteria and severity assessed with the Montgomery-Asberg Depression Rating Scale (MADRS). Forty-one (30.1%) of AT compared with 21 (35.0%) of the CI were depressed. The mean total MADRS score for AT was 23.90 standard deviation (SD) ±7.97 while the mean total MADRS score for the convicted was 25.50 SD ± 8.70, P= 0.479. Unlike the general population, there were no sociodemographic predictors of depression. Among the ATs, depression was associated with the presence of physical complaints, having a chronic illness and family history of psychiatric illness among the CI. The prevalence of depression among prisoners was found to be high and associated with clinical variables. Due attention needs to be given to address the mental health needs of the prisoners.